Ocular complications of antineoplastic therapies - Abbas Bader; Madeline Begemann; Ammar Al-Obaidi; Muhammad Hamza Habib; Faiz Anwer; Shahzad Raza (Future Science OA, 2023)
Ocular complications of antineoplastic agents can have a profound effect on the quality of life of cancer patients. New oncologic treatments like monoclonal antibodies, immunotherapies, antibody-drug conjugates, checkpoint inhibitors and growth factor receptors have resulted in increased ocular complications. These ocular complications differs in respect to distinct mechanisms of actions and lead to significant challenges in the management of cancer patients. In this review, we reviewed literature, clinical studies and cases detailing ocular complications due to administration of antineoplastic agents and emphasized the need for communication between oncologists and ophthalmologists toward early detection and management of ocular complications.